Badische Anilin- & Soda-Fabrik Hundert Mark Gutschein (Badische Anilin- & Soda-Fabrik, 1923)
This Hundert Mark Gutschein, or one hundred Mark voucher, was issued by Badische Anilin- & Soda-Fabrik. Styled after a banknote, the frontside includes an embossed stamp with the verso outlining the terms of the voucher. This particular voucher was issued at Badische Anilin- & Soda-Fabrik's main manufacturing facility in Ludwigshafen, Germany. Paper features a watermark design. As the first fully integrated chemical company in the world, Badische Anilin- & Soda-Fabrik was the world's largest chemical company by the the turn of the twentieth century. Ludwigshafen was the location of Badische Anilin- & Soda-Fabrik's main complex, which produced aniline dye. This German company scrip is an example of the hyperinflation which occurred in Germany after World War One as a result of reparation costs. Due to the devaluation of the Mark, companies began issuing their own currency that employees could use within their company stores. The high value of this currency is indicative of the hyperinflation of the Mark whose value decreased drastically from early 1923 through November 1923.
Keywords: Currency question; Chemical industry; Badische Anilin- & Soda-Fabrik; Corporations; Bauman, Robert Joel; Aniline